Medical student experiences of Case-Based Learning (CBL) at a multicultural medical school - Catherine Bruen; Jan Illing; Ronan Daly; Frances Meagher; Caroline Delany; Gozie Offiah; Sally Doherty; Ellen Stuart; Martina Crehan; Helen Kelly (BMC Medical Education)
Abstract Background Educational research highlights active approaches to learning are more effective in knowledge retention and problem-solving. It has long been acknowledged that adapting to more active ways of learning form part of the challenge for new university students as the pedagogical distance between the didactical approach largely followed by secondary school systems the world over differs quite significantly from the often more student-led, critical approach taken by universities. University students encounter various learning challenges, particularly during the transition from secondary school to university. Poor adaptation and low performance in the first year of tertiary education can lead to higher failure rates and potential withdrawal from study programmes. Adopting active learning strategies early in this transition phase is crucial for supporting students’ adaptation and success. Gaining student engagement with active learning can be a significant challenge when there is an expectation to participate in a discussion or voice an opinion. Case-based learning (CBL), with its scaffolded form of learning, is an approach that could provide the support needed to help multicultural learners adapt to their new learning environment in a non-threatening classroom-based setting. The research question in this study was: what features of CBL support active learning? Methods Data was collected using Structured Group Feedback Sessions (SGFS) from 36 students from 12 different countries. Students were placed in eight Structured Group Feedback sessions, a method that facilitates structured discussions and is effect in curriculum evaluation and feedback. The Experience Based Learning model was used as the conceptual framework to guide the analysis, which was completed using the framework analysis method. Results Themes were derived from the Experience Based Learning model: affective, pedagogical, and organisational and analysed according to the research question. We found CBL can be used to facilitate active learning with all students at a multicultural medical university. We identified six learning points to highlight features of CBL that support active learning: CBL increased contact with peers and facilitated student bonding; students need to feel psychologically safe to participate; prior learning can enhance confidence to participate; facilitators need to be aware of their role, know about psychological safety, and manage student participation including the dominant voice; some students have a lower tolerance of uncertainty and need additional clarity at the end either via the facilitator or additional notes that provide the key learning points to take away; students became more engaged when a case is aligned to a real patient case giving it authenticity. Conclusions This study explores how CBL can support active learning in a multicultural medical school. We identified that CBL did facilitate active learning and students engaged with it and enjoyed it. We identified six learning points to support others going forward.